Self-Rated Recovery and Mood Before and After Resistance Training and Muscle Microcurrent Application - Stößlein, Bernd A. C.; Kuypers, Kim P. C. (Frontiers in Psychology, 2022)
Background Resistance training (RT) can offer beneficial physiological and psychological effects. The regular continuation of this exercise can be accomplished by improving the recovery and mood after a workout. Frequency-Specific Microcurrent (microstimulation) might offer a solution here as it has been shown to improve physical injuries, mood state and sleep. However, knowledge is lacking about the impact of microstimulation after RT on said parameters. The present study aimed to test the effects of RT and muscle-microstimulation on mood and physical recovery in healthy men after performing conventional deadlifts, which is a type of RT. Methods The study was conducted according to a single-blind, randomized, placebo-controlled, two-way crossover study. Twenty participants naïve to microstimulation (MS) engaged in RT twice on separate days. They were randomized to receive MS on one day and no microstimulation (Sham-MS) on another day. Before and after the workout and after their treatment (MS or Sham-MS), participants self-rated their mood state and mental and physical exhaustion levels. Results Findings showed that MS increased the self-ratings of well-rested and sociable and, most importantly, reduced the feeling of exercise-induced exhaustion. There were no MS effects on ratings of feeling sad, happy, or exhausted, although the workout, independent of MS, negatively influenced the level of exhaustion. Conclusion The combination of enhanced sociableness, reduced fatigue, and exercise-induced exhaustion after a workout, followed by microstimulation, has important implications for professional sporters and nonprofessionals who try to get the best result after a workout. Future studies using a double-blind approach including different types of exercises, different durations of programs, and both sexes can shed more light on the full potential of microstimulation after a workout on mood state and exercise-induced exhaustion.